Employability rate of UMP graduates above 90% in past five years - Irene, Wei Kiong Ting (2019)
The employability rate of graduates from Universiti Malaysia Pahang (UMP), particularly Faculty of Computer Systems & Software Engineering (FSKKP) remains above 90% in the past five years. According to the national graduate employability (GE) survey, FSKKP, UMP has been performing well among all other universities in the country.